Measurement of Serum Chitinase 3 Like 1 Protien in Vitiligo Patients - Nagat Gaber Hemida; Abd-ElAziz El-Rifaie; Laila Rashed; Hanan Kamel (Egyptian Journal of Medical Research, 2022)
The aim of this work was to measure serum level of YKL-40 (CH3L1) protein as an inflammatory biomarker in vitiligo patients. 80 individuals from dermatology outpatient clinic at Beni-Suef University hospital were included in this study; 50 of them are vitiligo cases patients and 30 normal control persons. Blood samples were taken from each participant for measuring of YKL- 40. The serum level of CH3L1 in vitiligo patients was significantly higher as compared to normal control persons (p-value < 0.001); whereas the mean scores were (107.76 vs. 35.19) in cases and controls respectively